HIGH MOLECULAR CELLULOSE ESTERS. MECHANISM OF ACTION IN SUSTAINED RELEASE MATRIX TABLETS. DISSOLUTION PROFILE OF ACTIVE DRUG DEPENDING ON MOLECULAR WEIGHT AND HYDROPHILIC PROPERTIES OF POLYMERS - S. V. Trofimov (Фармация и фармакология (Пятигорск), 2015)
This article reviews cellulose esters as important excipients in development of dosage forms with sustained release. We have studied modern methods of drug development, based on technological, and physical and chemical properties of excipients to provide a sustained release effect and the mechanism of interaction between active substance and excipients for justification of choice of the optimum prolonging agent in compliance with desirable result. Different cellulose esters were used as model excipients. They were hydroxypropylmethylcellulose (HPMC) and hydroxyethylcellulose (HEC). we have studied an effect of molecular weight and hydrophilic properties on dissolution rate of active substance from the tablets with sustained release.